Effect of Different Dietary Energy Sources on Induction of Fatty Liver-Hemorrhagic Syndrome in Laying Hens - Zhang, Jinwei; Chen, Daiwen; Yu, Bing (International Journal of Poultry Science, 2008)
This experiment was conducted to determine the effect of different dietary energy sources on hepatic lipid content and induction of Fatty Liver-Hemorrhagic Syndrome in laying hens. One hundred and fifty Lohmann commercial layers were divided into three groups of fifty birds each. According to a single factorial arrangement, birds were given one of three experimental diets with control(group 1, 2.65Mcal/kg),or high energy diet which was offered with 7% lard (group 2, 3.06Mcal/kg) and offered with 26% cornstarch (group 3, 3.00Mcal/kg). High energy diets decreased feed intake and egg production (p<0.01), average egg weight of group 3 (cornstarch) was decreased (p<0.01); In chicks fed the 7% lard diet or 26% cornstarch ad libitum, hepatic EE (ether extract) and triglyceride were increased significantly, cornstarch could increase hepatic EE, triglyceride and total cholesterol more significant than lard. The average activity of ALT and AST of high energy was increased to be more than 2 times than control treatment of the last three times blood collection. The LDH of high energy diet was increased with no significant difference of the first three times blood collection. In our experiment, the birds fed the 7% lard diets had the largest increase in plasma triglyceride, but there were no significant treatment effects on plasma triglyceride content by cornstarch all the experiment period. The average hemorrhage score of group 2(lard diet) was the highest in the three groups. In chicks fed the 7% lard diet or 26% cornstarch ad libitum had significantly higher MDA values. In the present study, plasma ALT, AST, LDH activities and TC concentration were positively correlated with hepatic TG concentration (p<0.01). The results showed that measurement of enzyme activities indicative of liver damage in birds, particularly AST, ALT, and plasma TC concentration, is a valuable tool in the diagnosis of fatty liver-hemorrhagic syndrome in a flock of layers. These results suggest that dietary carbohydrate can induce FLHS more efficiently that dietary fat, the hens overfeed high fat diets have significantly more liver hemorrhage than high carbohydrate diets.